2018
DOI: 10.1021/acs.joc.8b00199
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of 5-Fluoropyrazoles from Pyrazoles and N-Fluorobenzenesulfonimide (NFSI)

Abstract: Facile synthesis of 5-fluoropyrazoles by direct fluorination of pyrazoles with N-fluorobenzenesulfonimide (NFSI) was elaborated. This approach was used to prepare the unsubstituted 5-fluoro-1 H-pyrazole, the known fungicide Penflufen, and many functionalized 5-fluoropyrazoles: building blocks for medicinal chemistry and agrochemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…In 2018, our group developed a practical synthesis of 5-fluoropyrazoles . In fact, N-protected pyrazoles were first treated with n BuLito generate a carbanionfollowed by addition of N -fluorobenzenesulfonimide (NFSI).…”
Section: Preparation Of Fluoro-substituted Pyrazolesmentioning
confidence: 99%
“…In 2018, our group developed a practical synthesis of 5-fluoropyrazoles . In fact, N-protected pyrazoles were first treated with n BuLito generate a carbanionfollowed by addition of N -fluorobenzenesulfonimide (NFSI).…”
Section: Preparation Of Fluoro-substituted Pyrazolesmentioning
confidence: 99%
“…Synthesis of 5-fluoropyrazoles typically occurs by reaction of (i) 1,3-dicarbonyl containing CF 3 /CF 2 (fluorinated synthon) with hydrazines followed by HF-elimination [8]; (ii) copper-catalyzed click reaction of fluorosydnones with alkynes [9]; (iii) Selectfluor and pyrazoles containing carboxylic acids followed by decarboxylation [10] and (iv) KF with pyrazoles [11,12]. The electrophilic fluorination of pyrazoles to give 5-fluoropyrazoles was recently described using N-fluorobenzenesulfonimide (NFSI) [13]. As shown in Figure 10 1-substituted pyrazoles were subjected to C5-deprotonation by lithium base, which was then fluorinated using NFSI to yield 1-substituted-5-fluoropyrazoles [13].…”
Section: C5-electrophilic Fluorination Of Pyrazolesmentioning
confidence: 99%
“…The electrophilic fluorination of pyrazoles to give 5-fluoropyrazoles was recently described using N-fluorobenzenesulfonimide (NFSI) [13]. As shown in Figure 10 1-substituted pyrazoles were subjected to C5-deprotonation by lithium base, which was then fluorinated using NFSI to yield 1-substituted-5-fluoropyrazoles [13].…”
Section: C5-electrophilic Fluorination Of Pyrazolesmentioning
confidence: 99%
“…Following these works, Mykhailiuk et al reported a one-pot synthesis of biologically important 5-uoropyrazoles 17 by direct lithiation/uorination of the corresponding pyrazoles 16 employing n BuLi as the lithium and NFSI as the uorine source. 32 The method was general and, as shown in Scheme 9, under the optimized conditions, various N-aryl and N-alkyl substituted pyrazole derivatives were selectively uorinated at the C5-position with moderate to good yields. However, N-alkyl pyrazoles bearing sterically bulky substituents (e.g., N-tert-butylpyrazole) failed to give the desired uorinated products.…”
Section: Transition-metal-free Reactionsmentioning
confidence: 99%